2022
DOI: 10.1038/s41393-022-00776-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of transcutaneous electrical nerve stimulation in people with pain after spinal cord injury: a meta-analysis

Abstract: Study Design Meta-analysis. Objectives This study aimed to evaluate the effect of transcutaneous electrical nerve stimulation in people with pain after spinal cord injury by meta-analysis. Methods Reviewed PubMed, Embase, Cochrane library, as well as China National Knowledge Infrastructure (CNKI), Wanfang, and Vip databases to search the randomized controlled trials of pain after spinal cord injury through transcuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(29 reference statements)
0
7
0
1
Order By: Relevance
“…TENS is proposed to provide its analgesic effect through maintenance of spinal opioid receptors through inhibition of mitogen activated protein kinase and proinflammatory expression, activation of glial cells to release inhibitory neurotransmitters, and reduction in dorsal horn neuron activity ( 119 121 ). Recent metanalysis involving six randomized-controlled trials and 165 cases revealed favorable results for the use TENS in pain secondary to SCI ( 122 ). The difference in VAS between the observation and controlled groups was statistically significant and the short-form McGill pain questionnaire (SF-MPQ) was generally lower in the TENS groups in comparison to the control groups ( 122 ).…”
Section: Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…TENS is proposed to provide its analgesic effect through maintenance of spinal opioid receptors through inhibition of mitogen activated protein kinase and proinflammatory expression, activation of glial cells to release inhibitory neurotransmitters, and reduction in dorsal horn neuron activity ( 119 121 ). Recent metanalysis involving six randomized-controlled trials and 165 cases revealed favorable results for the use TENS in pain secondary to SCI ( 122 ). The difference in VAS between the observation and controlled groups was statistically significant and the short-form McGill pain questionnaire (SF-MPQ) was generally lower in the TENS groups in comparison to the control groups ( 122 ).…”
Section: Modalitiesmentioning
confidence: 99%
“…Recent metanalysis involving six randomized-controlled trials and 165 cases revealed favorable results for the use TENS in pain secondary to SCI ( 122 ). The difference in VAS between the observation and controlled groups was statistically significant and the short-form McGill pain questionnaire (SF-MPQ) was generally lower in the TENS groups in comparison to the control groups ( 122 ). In addition to pain, peripheral nerve stimulation in persons with SCI has also been reported to improve lower extremity muscle mass, spasticity, neurogenic bladder, and respiratory function ( 116 , 123 126 ).…”
Section: Modalitiesmentioning
confidence: 99%
“…The use of TENS in pain treatment is well-studied and mostly consists of delivering low-frequency electrical pulses to the affected area. A recent meta-analysis, including six RCTs with 165 patients, indicated that visual analog scale (VAS) for pain and short-form McGill pain questionnaire scores were significantly reduced in SCI patients who received TENS compared with the control group [75]. In addition to pain, prior evidence supports the use of TENS in improving spasticity [76].…”
Section: Transcutaneous Electrical Nerve Stimulationmentioning
confidence: 99%
“…Otras intervenciones que se pueden considerar como coadyuvantes en el tratamiento del dolor son la hipnosis, la meditación, la biorretroalimentación y la atención plena (mindfulness), entre otros 41 . El uso de la estimulación eléctrica transcutánea (TENS) puede disminuir levemente y a corto plazo el DN 42 . La estimulación cerebral no invasiva, mediante la aplicación de pequeñas cantidades de corriente o la estimulación magnética transcortical, han demostrado disminuir el dolor, aunque con magnitudes de efecto moderadas 43,44 .…”
Section: Instauración De Tratamientos Y Pronósticounclassified